EDUCATION ADMINISTRATION REFORM: A CASE STUDY ON THE IMPLEMENTATION OF THE MERDEKA CURRICULUM - Arkam Lahiya; Opan Arifudin; Tiara Fathulmila Matiala (INJOSEDU: International Journal of Social and Education, 2025)
The implementation of Merdeka Curriculum in Indonesia represents an important effort in reforming education administration to improve learning quality. This research highlights curriculum flexibility as key in building a learning environment that is more adaptive and responsive to students' needs. The freedom for educators to customise teaching materials and methods facilitates more relevant and contextualised learning. However, significant challenges remain, including limited infrastructure and educator readiness. The results of this study emphasise the need for ongoing support and training for teachers for the reforms to be effective. Ultimately, Merdeka Curriculum has the potential to be a catalyst for positive change if supported by adequate management and resources.